Impacts des systèmes agroforestiers sur les propriétés physico-chimiques, hydriques et la fertilité des sols en milieux semi-arides Cas de la plaine des Bordjias (Mesra, W. de Mostaganem) - FETTOUCH Dalila (My University, 2016)
All the problems, related to conventional agriculture are a reference to the search for the sustainable solutions. In this context, a comparative study between three agroforestry systems (Citrus sinensis, Olea europaea and Punica granatum each associated with Vicia faba) was conducted in the plain of Bordjias. In order to study the impacts of each system on physic-chemical properties, water and soil fertility, the soil samples were taken from two plots (on and off the tree), through three horizons (Sh, Mh and Lh), before and after the establishment of culture (Vicia faba) with follow-up of its growth, and performance estimate. The results show that the moisture variability appears to be influenced by the position, the type of soil and the woody species. By increasing the organic matter content, these associations improve the structural stability of the soil, accelerating the process of dissolution of calcium carbonate, changing the pH, EC, the P2O5, CEC, balancing cations and ion exchange in soil. The statistical approach (ANOVA) allowed us to bring out the importance of relations between the trees in general and agroforestry systems in particular with soil fertility. Thus, agroforestry combining on the same plots mixed vocation of annual agricultural production, and deferred long-term production by trees, offers the new perspectives for a different agricultural, productive and environmentally friendly
Keywords: Agroforestry, fertility, soil, environments semi-arid, plain Bordjias.